The Relationship Between Leisure Time use and Life Satisfaction of the Elderly from Foreign Studies and Policy Implications for Vietnam - Thuan, Phan (VNU Journal of Science: Policy and Management Studies, 2022)
Leisure time use has many benefits for personal and social development. Therefore, leisure time use of the elderly also has positive signification for their lives. By literature review method, the article identifies the current status of leisure time use and its benefits to the elderly's life. The article clearly shows that participating in free time activities helps the elderly reduce depression, improve health and reduce loneliness. Hence, the more active old people participate in leisure activities (exercise, social and cultural activities, etc,…), the higher the life satisfaction is. On this basis, some recommendations with policy implications are proposed to help the elderly have a better life in their final years. Keywords The Elderly, Leisure time use, the life satisfaction, the relationship between leisure time use and life satisfaction. References [1] C. Khac, Issues of Time Budget in Daily Family Activities, Journal of Sociology, No. 3-4, 1998, pp. 97-101 (in Vietnamese). [2] C. Dridea, G. Sztruten, Free Time- the Major Factor of Influence for Leisure, Romanian Economic and Business Review, Vol. 5, No.1, 2013, pp. 210. [3] J. Kelly, Leisure, 3rd Edition. Boston and London: Allyn and Bacon, ISBN 978-0-13-110561-4, 1996, pp. 17-27, [4] N. T. Minh, The Reality of Using Free Time of Rural People in the Northern Delta (Case Study of Trinh Xa Commune, Binh Luc District, Ha Nam Province), Journal of Sociology, No. 4, 2009, pp. 61 (in Vietnamese). [5] L. N. Van, Happiness of Vietnamese, General Publishing House, Ho Chi Minh City, 2019 (in Vietnamese). [6] D. C. Shin, D. M. Johnson, Avowed Happiness as an Overall Assessment of Life, Social Indicators Research, Vol. 5, 1978, pp. 478. [7] E. Diener, R. A. Emmons, R. J. Larsen, S. Griffin, The Satisfaction with Life Scale, Journal of Personality Assessment, Vol. 49, 1985, pp. 71-75. [8] N. T. X. Mai, Measurement of Satisfaction with Life, http://consosukien.vn/do-luong-su-hai-long-voi-cuoc-song.htm/, 2021 (accessed on: February 16th, 2021) (in Vietnamese). [9] T. D. Luan, Some Research Issues on the Elderly from Sociological perspective, Journal of Sociology, No. 2, 1992, pp. 63-67 (in Vietnamese). [10] WHO, Active Aging, A Policy Framework, a Contribution of the World Health Organization (WHO) to the second United Nations World Assembly on Aging, 2002, pp. 12, http://whqlibdoc.who.int/hq/2002/WHO NMH NPH 02.8.pdf (accessed on: February 16th, 2021). [11] G. Sala, D. Jopp, F. Gobet, M. Ogawa, Y. Ishioka, Y. Masui, H. Inagaki, T. Nakagawa, S. Yasumoto, T. Ishizaki, Y. Arai, K. Ikebe, K. Kamide, Y. Gondo, The Impact of Leisure Activities on Older Adults’ Cognitive Function, Physical Function, and Mental Health, POLS ONE, Vol. 14 No. 11, 2019, pp 1-13. [12] S. Lida, Structure of Life Satisfaction from the Perspective of Arts Experiences in Japan, Palgrave Communications, No. 143, 2019, pp. 1-8, https://doi.org /10.1057/s41599-019-0354-2. [13] P. Thieme, D. A. V. Dittrich, A Life – Span Perspective One Life Satisfaction. SOEPpapers on Multidisciplinary Panel Data Research 775, DIW Berlin, The German Socio-Economic Panel (SOEP), 2015. [14] T. Joloza, Measuring National Well-being: Older People’s Leisure Time and Volunteering, Report, Office of National Statistics, 2013. [15] A. Punyakaew, S. Lersilp, S. Putthinoi, Active Aging Level and Time Use of Elderly Persons in a Thai Suburban Community, Occupational Therapy International, No. 2, 2019, pp. 1-8. [16] M, Tadie, G. M. W. Oerlemans, N. A. Barker, R. Veenhoven, Daily Activities and Happiness in Later Life: The Role of Work Status, Journal Happiness Study, Vol. 14, 2012, pp. 1507-1527. [17] Y. J. Cha, Correlation Between Leisure Activity Time and Life Satisfaction: Based on KOSTAT Time Use Survey Data, Occupational Therapy International, Vol. 2018, 2018, pp. 1-9, https://doi.org/10.1155/2018/5154819. [18] D. Kaufman, M. O. Chang, A. Ireland, Leisure Time use, Meaning of Life and Psychological Distress: Comparing Canadian and Korean Older Adults, Journal of Education and Culture Studies, Vol. 2, No. 4, 2018, pp. 327-346. [19] H. A. Guathier, M. T. Smeeding, Time Use at Older: Cross – National differences, Research on Aging, Vol. 25, No. 3, 2003, pp. 249. [20] J. H. Lee, J. H. Lee, S. H. Park, Leisure Activity Participation as Predictor of Quality of Life in Korean Urban – Dwelling Eldrly, Occupational Therapy international, Vol. 21, No. 3, 2014, pp. 124-132. [21] K. R. Kent, J. Stewart, How Do Older Americans Spent Their Time?, Monthly Labor Review, May, 2007, pp. 8-26. [22] J. Verghese, B. R. Lipton, J. M. Katz, B. C. Hall, A. C. Derby, K. G. Sky, F. A. Ambrose, M. Sliwinski, H. Buschke, Leisure Activities and The risk of Dementia in the Elderly, the New England Journal of Medicine, No. 385, 2003, pp. 2508-2516. [23] S. Ana, S. Rusac, S. Ana, Spending Leisure Time in Retirement. Periodicum biologorum, Vol. 115, No. 4, 2013, pp. 568. [24] X. Wei, S. Huang, M. Stodolska, Y. Ya, L. Time, Leisure Activities, and Happiness in China: Evidence from a National Survey, Journal of Leisure Research, Vol. 47, No. 5, 2015, pp. 562. [25] H. A. Gautheir, M. T. Smeeding, Patterns of Time Use of People Age 55 to 64 Years Old: Some Cross- National Comparisons, Aging Studies Program Paper, No. 20, 2000. [26] P. Arriagada, A Day in the Life: How Do Older Canadians Spend Their Time?, https://www150.statcan.gc.ca/n1/pub/75-006-x/ 2018001/article/54947-eng.htm/, 2020, (accessed on: March 29th, 2020). [27] S. Stobert, D. Dosman, N. Keating, General Social Survey on Time Use: Cycle19. Aging Well: Time Use Patterns of Older Canadians (catalogue no. 89-622-XIE), Ottawa, ON: Statistics Canada, 2005, Retrieved from, http://www.statcan.gc.ca (accessed on: March 29th, 2020). [28] Z. Zhang, Z. Qiu, Exploring Daily Activity Patterns on the Typical Day of Older Adults for Supporting Aging-in-Place in China’s Rural Environment, International Journal of Environmental Research and Public Health, Vol. 17, No. 22, 2020, pp. 8416, https://doi.org/10.3390/ijerph17228416. [29] E. M. Paggi, D. Jopp, C. Hertzog, The Importance of Leisure Activities in the Relationship Between Physical Health and Well-being in a Life Span Sample, Behavioral Science section, Original Paper, No. 62, 2016, pp. 450. [30] B.Singh, V. U. Kiran, Recreational Activities for Senior Citizens, Journal of Humanities and Social Science, Vol.19, No. 14, 2014, pp. 24-30. [31] Z. Li, C. Zhenhui, The Impact of Leisure Activities on Chinese Elderly's Cognitive Function, Journal of Psychological Science, Vol. 9, No. 5, 2017, pp. 727-739. [32] K. Y. Choo, Korean People’s Leisure Time Change During 1981-2000, Paper Presented at the Annual Conference of the International Association for Time Use Research (IATUR), Lisbon, Portugal, 2002. [33] J. Y. J. Wang, D. H. D. Zhou, J. Li, M. Zhang, J. Deng, M. Tang, M. Chen, Leisure Activity and Risk of Cognitive Impairment: The Chongqing Aging Study, Neurology, Vol. 66, No. 6, 2006, pp. 911 -913. [34] M. O. Chang, The Effect of Older people’s Internet Uses and Gratification on Social Activities. Andragogy Today, Vol. 7, No. 3, 2004, pp. 133-154. [35] A. K. Forsman, F. Nyqvist, I. Schierenbeck, Y. Gustafson, K. Wahlbeck, Structural and Cognitive Social Capital and Depression Among Older Adults in Two Nordic Regions, Aging & Mental Health, Vol. 16, No. 6, 2012, pp. 771-779. [36] H. M. Jaafar, H. M. Romil, Using Technology to Help the Elderly Cope with Loneliness. https://www.thestar.com.my/lifestyle/health/2019/11/21/technology-helps-combat-loneliness-among-elderly/, 2020, (accessed on: March 15th, 2020). [37] M. J. Dergance, L. W. Calmbach, R. Dhanda, P. T. Miles, H. P. Hazuda, P. C. Mouton, Barries to and Venefits of Leisure Time Physical Activities in the Elderly: Difference Across Culture, Journal of the American Geriatrics Society, Vol. 51, No. 6, 2003, pp. 863-868. [38] H. W. Roh, C. H. Hong, Y. Lee, K. S. Lee, K. J. Chang, S. J. Son, Participation in Physical, Social, and Religious Activity and Risk of Depression in the Elderly: A Community-based three-year Longitudinal Study in Korea, PLoS ONE, Vol. 10, No. 7, 2015, pp. 1-13, https://doi.org/10.1371/journal.pone.0132838. [39] N. R. Smith, G. Kielhofner, H. J. Watts, The Relationships Between Volition, Activity Pattern and Life Satisfaction in the Elderly, The American Joural of Occpational Therapy, Vol. 40, 1986, pp. 278-283. [40] N. B. Sajin, A. Dahlan, A. S. S. Ibrahim, Quality of life and leisure Participation Amongst Malay Older People in the Institution, AMER International Conference on Quality of life, AicQoL2016Medan, Procedia – Social and Behavioral Science, Vol. 234, 2016, pp. 83-89. [41] N. P. Blace, Functional Ability, Participation in Activities and Life Satisfaction of the Older People., Canadian Center of Science and Education, Vol. 8, No. 3, 2012, pp. 75-87. [42] H. Yoon, W. S. Lee, K. B. Kim, J. Moon, Effects of Leisure Participation on Life Satisfaction in Older Korean Adults: A Panel Analysis, International Journal of Environmental Research and Public Health, No. 17, 2020, pp. 1-9. [43] General Statistics Office, Population and Housing Census Results in 2019, Statistical Publishing House, Hanoi, 2020, pp. 626-624 (in Vietnamese). [44] Communist Party of Vietnam, Document of the 13th National Congress of Deputies, National Political - Truth Publishing House, Hanoi, Vol. 2, 2021 (in Vietnamese). [45] B. T. Cuong, Elderly Women in Rural Areas, Journal of Sociology, No. 2, 1992, pp. 21-25 (in Vietnamese). [46] V. H. Thach, Some Social Problems of Widowed Elderly in Family and Community Relations, Journal of Sociology, No. 2, 1997, pp. 60-69 (in Vietnamese). [47] B. Q. Nga, Elderly people in Central and Southern Vietnam Biet Nam year 2000- Outline from Some Qualitative Studies, Journal of Sociology, Vol. 3, No. 73, 2001, pp. 28-39 (in Vietnamese). [48] P. Thuan, Social life of the Elderly in the Mekong Delta in the Context of Population Aging, Southern Journal of Social Sciences, No. 4, 2020, pp. 24-32. (in Vietnamese).